Effect of interaction of herb (Pueraria tuberosa) components with milk constituents on properties of milk: physicochemical properties of herb-milk model system - sawale, Pravin; N, Veena; singh, RRB; Arora, Sumit (Indian Journal of Dairy Science, 2024)
Milk is a carrier which has been effectively used to deliver phytochemicals for targeted health benefits in the traditional Indian systems of medicine, particularly Ayurveda. The model system consisted of cow milk fortified with aqueous extract of Pueraria tuberosa (@ 0.4%) on the basis of sensory evaluation by using 9-point hedonic scale. Effect of addition of herb on compositional and storage stability of control and experimental milk was investigated. The interactive effect of milk proteins with Pueraria tuberosa extract (@0.4%) was also studied by SDS-PAGE and urea-PAGE electrophoresis.The addition of Pueraria tuberosa to milk resulted in no change in composition, increase in phenol content and decrease in pH (during successive period of storage) as compared to control. Electrophoretic pattern of sodium caseinate and whey protein concentrate containing 0.4% herb extract showed that the band width changed in terms of height and volume. It can be concluded that addition of Pueraria tuberosa to milk at 0.4% concentration altered the functional properties of milk which could be due to interaction of components of Pueraria tuberosa with milk constituents.